2017
DOI: 10.1590/s0100-736x2017000900013
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of β-glucan and glutamine on intestinal and immunological damage in mice induced by cytarabine (Ara-C)

Abstract: Recently, glutamine and β-glucan have been demonstrated to play an important role in modulation of the immune system and in promoting intestinal health benefits. The aim of this study was to investigate the effect of this intervention on inflammatory responses and intestinal health in mice orally pretreated with soluble Saccharomyces cerevisiae derived 1,3/1,6-β-glucan (80mg/kg) with or without glutamine (150mg/kg) and then challenged with cytarabine (Ara-C) (15mg/kg). Improvements in villi and crypts were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This proves that glutamine can reduce inflammatory reactions in the intestine, both in acute and chronic diarrhea. This result is supported by a study by Mariana et al in 2017 which induced inflammation in the intestines of rats with 15 mg/kg cytarabine commonly used as a therapy for leukemia and lymphoma in humans, the rats were then treated with glutamine therapy at a dose of 150 mg/kg/day for 21 days and the administration of glutamine was found to reduce inflammation and increase the immune response in the intestine [20].…”
Section: Discussionsupporting
confidence: 56%
“…This proves that glutamine can reduce inflammatory reactions in the intestine, both in acute and chronic diarrhea. This result is supported by a study by Mariana et al in 2017 which induced inflammation in the intestines of rats with 15 mg/kg cytarabine commonly used as a therapy for leukemia and lymphoma in humans, the rats were then treated with glutamine therapy at a dose of 150 mg/kg/day for 21 days and the administration of glutamine was found to reduce inflammation and increase the immune response in the intestine [20].…”
Section: Discussionsupporting
confidence: 56%
“…Supplementation of beta-glucan and MOS from SCYS or YCWP improves mammary gland health in lactating animals [50,52,56,66]. Moreover, orally taking SCY-derived beta-glucan has been reported to influence the synthesis and release of interleukins IL-6 and IL-10 in vivo [98][99][100] and reduce blood IL-6 and increase blood IL-10 in overweight and obese people [101]. These cytokines were also detected in breast milk and may potentially regulate infant gut immunity [102], although no maternal supplementation studies have evaluated human milk cytokines.…”
Section: Hypotheses Of the Mechanism Of Saccharomyces Cerevisiae Yeast-based Supplement On Breast Milk Productionmentioning
confidence: 99%
“…Previous research showed a decline in the levels of inflammatory cytokines, such as TNF‐α and IL‐10, in humans after surgery and supplemented with glutamine (Wilmore, 2001). In mice, pre‐treated orally with glutamine before a challenge, showed the IL‐10 blood levels did not change, despite increasing count of leucocytes in comparison to the group without treatment (Porsani et al., 2017). Although when evaluating this amino acid supplementation in human patients on post‐operative period, conflicting results were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding supplementation with high concentrations of glutamine, no clinical research in dogs has been conducted. However, controversial results have been described in laboratory animals and human patients supplemented with this nutrient (Klek et al., 2008; Lu et al., 2011; Porsani et al., 2017; Wilmore, 2001). Previous research showed a decline in the levels of inflammatory cytokines, such as TNF‐α and IL‐10, in humans after surgery and supplemented with glutamine (Wilmore, 2001).…”
Section: Discussionmentioning
confidence: 99%